2022
DOI: 10.1177/03009858221083038
|View full text |Cite
|
Sign up to set email alerts
|

Canine and murine models of osteosarcoma

Abstract: Osteosarcoma (OS) is the most common malignant bone tumor in children. Despite efforts to develop and implement new therapies, patient outcomes have not measurably improved since the 1980s. Metastasis continues to be the main source of patient mortality, with 30% of cases developing metastatic disease within 5 years of diagnosis. Research models are critical in the advancement of cancer research and include a variety of species. For example, xenograft and patient-derived xenograft (PDX) mouse models provide op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 181 publications
(281 reference statements)
0
29
0
Order By: Relevance
“…To date, research evaluating PIs in OS are predominately preclinical and have employed both human and canine models [ 45 ]. Being in close quarters with humans, canines are exposed to similar environmental factors [ 75 , 76 ]. They offer a natural way to study the disease and are evolutionarily closer to humans in comparison to rodent models [ 75 , 76 ].…”
Section: Pis Used In Cancer Treatment and Evidence For Their Use In Osmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, research evaluating PIs in OS are predominately preclinical and have employed both human and canine models [ 45 ]. Being in close quarters with humans, canines are exposed to similar environmental factors [ 75 , 76 ]. They offer a natural way to study the disease and are evolutionarily closer to humans in comparison to rodent models [ 75 , 76 ].…”
Section: Pis Used In Cancer Treatment and Evidence For Their Use In Osmentioning
confidence: 99%
“…Being in close quarters with humans, canines are exposed to similar environmental factors [ 75 , 76 ]. They offer a natural way to study the disease and are evolutionarily closer to humans in comparison to rodent models [ 75 , 76 ]. Similar to humans, OS in canines is also considered uncommon; however, it occurs much more frequently in canines compared to humans [ 77 ].…”
Section: Pis Used In Cancer Treatment and Evidence For Their Use In Osmentioning
confidence: 99%
“…It has been reported that OSA occurs in long bones of the appendicular skeleton near the metaphyseal growth plates, and the distal portion of the femur and the proximal tibia are the most affected sites in humans [34]. In humans, OSA appears primarily in adolescence, with most cases between the ages of 10 and 14, suggesting a close relationship between early pubertal rapid bone growth and tumor development [35] with a higher risk in taller children [36].…”
Section: Comparison Of Canine and Human Osamentioning
confidence: 99%
“…While experimental cancer models used in carefully controlled studies will continue to be essential to assess the toxicology, mechanisms, and initial antitumor activity of cancer drugs, there is a crucial need for additional complementary models that more closely represent human cancer. Pet dogs with specific forms of naturallyoccurring cancer are rapidly emerging as complementary animal models for cancer treatment research as canine cancer more closely mimics human cancer in pathological, cellular, and molecular features; cancer heterogeneity; aggressive metastatic behavior; host immunocompetence; and treatment response (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Dogs are also large enough for procedures such as those involving surgery, endoscopy, various imaging modalities, and the evaluation of medical devices.…”
Section: Introductionmentioning
confidence: 99%